Gambaran Penatalaksanaan Oral Hygiene Pada Penderita Stroke Di Rsud Dr. Moewardi Surakarta - Purwati, Zwastika Yesi; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Stroke was a multifactor disease with a variety of causes with major clinical manifestations, and the leading cause of disability and death in developing countries. In stroke patients, physical weakness, a major problem limitations to mobilize. One was in trouble with swallowing and paralysis of the face can increase the amount of bacteria in the mouth from the remnants of the food there. In hospital stroke patient's inability to meet the needs of himself into the nurse's responsibility. This study aims to describe the management of oral hygiene by nurses in stroke patients at the General Hospital Dr. Moewardi. This study was an observational descriptive research with quantitative approach. Samples were 24 nurses in the technique of the total population. Collecting data using observations were analyzed using descriptive test. Conclusion of the study was (1) the characteristics of nurses in Ward Orchid 2 Hospital Dr. Moewardi Surakarta is female, educated S1 Profession nurses , and has a long working less than 10 years and (2) management of oral hygiene in patients with stroke in Hospital Dr. Moewardi Surakarta was largely quite, while managing less attention among other nurses did not inquire the condition of the patient's mouth after cleaning, wash hands before carrying out oral hygiene, did not identify patients with a better, less maintaining the privacy of patients, oral hygiene part in less attention. Keywords: stroke patients, oral hygiene, management, nurse